Analysis of the use of Daif Hadith in the fatwa on Islamic inheritance law (Faraid) in Malaysia - Fathullah Asni,; Jasni Sulong,; Ammar Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study examines the status of hadith that can be used as an argument in fatwa involving legal (hukm) affairs and evaluates the status of the hadiths used in the fatwas of Islamic inheritance law (faraid) issued by state Mufti departments. This study was conducted based on recorded previous studies on the use of daif hadith in fatwa related to the issue of will (wasiat), and its significant effect in violating the principles of fatwa and causing differences in fatwas on the same issues. The methodology of this study is qualitative, by which the data were collected through library research and field studies. The library research was done by examining books of usul al-fiqh, hadith, articles, enactments, and related circulars, while field studies were conducted using unstructured interview method with selected Muftis. The findings show three decided fatwas on faraid issues by state Mufti departments; the issue of inheritance to dhu arham heirs; the issue of nominee status in EPF; and the issue of remuneration, compensation, and consolation status in faraid. However, only the issue of inheritance to dhu arham heirs used arguments from the hadith. The study also found three out of five Mufti departments argued with daif hadith in the fatwa on issue of inheritance to dhu arham heirs, while the other two state Mufti departments argued on the authenticity (sahih) of the hadith in the issue of the matter.